2015
DOI: 10.1038/srep10971
|View full text |Cite
|
Sign up to set email alerts
|

Integrative proteomics to understand the transmission mechanism of Barley yellow dwarf virus-GPV by its insect vector Rhopalosiphum padi

Abstract: Barley yellow dwarf virus-GPV (BYDV-GPV) is transmitted by Rhopalosiphum padi and Schizaphis graminum in a persistent nonpropagative manner. To improve our understanding of its transmission mechanism by aphid vectors, we used two approaches, isobaric tags for relative and absolute quantitation (iTRAQ) and yeast two-hybrid (YTH) system, to identify proteins in R. padi that may interact with or direct the spread of BYDV-GPV along the circulative transmission pathway. Thirty-three differential aphid proteins in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 62 publications
0
66
0
1
Order By: Relevance
“…In addition, heritable aphid and endosymbiont proteins are found to be implicated in the transmission of circulative polerovirus (Cilia et al ., ). Integrative proteomics can be used to uncover the mechanism of barley yellow dwarf virus‐GPV by the aphid Rhopalosiphum padi (Wang et al ., ). Furthermore, proteomic studies of the interaction between rice stripe virus and the vector, the small brown planthopper ( Laodelphax striatellus ), provide evidence for new functions of a hemipetran cuticular protein (Liu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, heritable aphid and endosymbiont proteins are found to be implicated in the transmission of circulative polerovirus (Cilia et al ., ). Integrative proteomics can be used to uncover the mechanism of barley yellow dwarf virus‐GPV by the aphid Rhopalosiphum padi (Wang et al ., ). Furthermore, proteomic studies of the interaction between rice stripe virus and the vector, the small brown planthopper ( Laodelphax striatellus ), provide evidence for new functions of a hemipetran cuticular protein (Liu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Protein function classification was based on the annotation from UniProt67. The subcellular localization was the integration of prediction results through WoLF PSORT (http://www.genscript.com/wolf-psort.html), Plant-mPLoc (http://www.csbio.sjtu.edu.cn/bioinf/plant-multi/)68 and UniprotKB.…”
Section: Methodsmentioning
confidence: 99%
“…A CP of the hemipteran vector, Laodelphax striatellus , was found to interact with the nucleocapsid protein (pc3) of Rice stripe virus (genus Tenuivirus , family Phenuiviridae ) and was hypothesized to be involved in viral transmission and to possibly protect the virus from degradation by a host immune response in the hemolymph (19). Recently, a CP of another hemipteran vector, Rhopalosiphum padi , was identified to interact with Barley yellow dwarf virus-GPV (genus Luteovirus , family Luteoviridae ) readthrough protein, and the gene transcript of this particular CP was differentially expressed in viruliferous compared to virus-free aphids (38). At the transcript level, thrips cuticular proteins of different types - including the thrips CPRs used in the present study to phylogenetically place the three cuticular TIPs - were identified to be downregulated in TSWV-infected first instar larvae (18).…”
Section: Discussionmentioning
confidence: 99%